THE RELEVANCE OF THE MEANING OF STATE DEFENSE IN DIGITAL PUBLIC PERCEPTION - Laode Muhamad Fathun; Danis T. Saputra Wahidin; Chairun Nisa Zempi (LPSDI Bina Patria, 2023)
This study aims to explain the relationship of public expression and interpretation to the meaning of State Defense in the digital era. This study used quantitative methods to a number of respondents who were selected. This study took a sample of social media as a medium to capture the National Defense of the Digital Public. The results found that about more than 3 percent of the people expected to be a role of State Defense in governance. Then about more than 8 percent who rated State Defense as a negative activity and there were about more than 58 percent who chose neutral. Thus State Defense is still expected as an adhesive element of the nation to rebuild sovereign, justice and prosperous governance